Cell-cell contacts prevent t-BuOOH-triggered ferroptosis and cellular damage in vitro by regulation of intracellular calcium - Faust, Dagmar; Wenz, Christine; Holm, Stefanie; Harms, Gregory; Greffrath, Wolfgang; Dietrich, Cornelia (Archives of toxicology, 2024)
Tert-butyl hydroperoxide (t-BuOOH) is an organic hydroperoxide widely used as a model compound to induce oxidative stress. It leads to a plethora of cellular damage, including lipid peroxidation, DNA double-strand breaks (DNA DSBs), and breakdown of the mitochondrial membrane potential (MMP). We could show in several cell lines that t-BuOOH induces ferroptosis, triggered by iron-dependent lipid peroxidation. We have further revealed that not only t-BuOOH-mediated ferroptosis, but also DNA DSBs and loss of MMP are prevented by cell-cell contacts. The underlying mechanisms are not known. Here, we show in murine fibroblasts and a human colon carcinoma cell line that t-BuOOH (50 or 100 µM, resp.) causes an increase in intracellular Ca2+, and that this increase is key to lipid peroxidation and ferroptosis, DNA DSB formation and dissipation of the MMP. We further demonstrate that cell-cell contacts prevent t-BuOOH-mediated raise in intracellular Ca2+. Hence, we provide novel insights into the mechanism of t-BuOOH-triggered cellular damage including ferroptosis and propose a model in which cell-cell contacts control intracellular Ca2+ levels to prevent lipid peroxidation, DNA DSB-formation and loss of MMP. Since Ca2+ is a central player of toxicity in response to oxidative stress and is involved in various cell death pathways, our observations suggest a broad protective function of cell-cell contacts against a variety of exogenous toxicants.
Online veröffentlicht: 30. Mai 2024
Gesehen am 13.11.2024